ASICs Alteration by pH Change in Trigeminal Ganglion Neurons - Junsre, Uggrit; Bongsebandhu-phubhakdi, Saknan (Journal of Physiological and Biomedical Sciences, 2014)
The inflammatory events associated with the pathophysiology of headache, which involve afferents of trigeminal ganglion (TG) neurons, lead to pH drop and cause a local tissue acidosis. It is known that acid-sensing ion channels (ASICs) play a major role of sensor in response to pH change, which can activate the nociceptor in the local tissue acidosis at pH 7.0. However, how ASICs can activate TG neurons when pH change is still unclear. Thus, we investigated the effect of pH change (from pH 7.4 to pH 7.0) to small-and-medium-sized (15-80 pF) and large-sized (> 80 pF) TG neurons, which were grouped as nociceptive and non-nociceptive neurons, respectively. Primary-cultured TG neurons were subjected to whole-cell recording by patch clamp technique that injected depolarizing current steps in long periods. The electrophysiological properties of TG neurons were compared in the condition of pH 7.0 and pH 7.4. The results revealed that resting membrane potential (RMP) of small-and-medium-sized TG neurons was significantly depolarized in pH 7.0. Moreover, threshold hyperpolarization and threshold current reduction were observed. In contrast to small-and-medium-sized TG neurons, large-sized neurons did not response to pH change. These finding suggested that pH change can modulate the excitability of nociceptive neurons resulting in the increase of pain perception in trigeminal pathway.